A Case of Subcutaneous Granuloma Annulare (SGA) in the Scalp of a Child: Histological Findings. (3rd September 2015) - Shokouhi, Behrouz; Vahedi, Amir; Esmaily, Heidar Ali
Abstract : Subcutaneous granuloma annulare is type of granuloma annulare which usually occurs in children. Scalp involvement is rare. The authors report a 3-year-old girl with subcutaneous granuloma annulare confirmed by imaging and histologic findings. No treatment was provided. The patient was followed for 6 months with no considerable complications.